Suppressor of cytokine signaling 1 (SOCS1) limits NFκB signaling by decreasing p65 stability within the cell nucleus - Strebovsky, Julia; Walker, Patrick; Lang, Roland; Dalpke, Alexander (The FASEB journal, 2011)
Suppressor of cytokine signaling (SOCS) proteins are inhibitors of cytoplasmic Janus kinases (Jak) and signal transducer and activator of transcription (STAT) signaling pathways. Previously the authors surprisingly observed that SOCS1 translocated into the nucleus, which was because of the presence of a nuclear localization sequence. This report now hypothesizes that SOCS1 mediates specific functions within the nuclear compartment because it is instantly transported into the nucleus, as shown by photoactivation and live cell imaging in human HEK293 cells. The NFkB component p65 is identified as an interaction partner for SOCS1 but not for other members of the SOCS family. SOCS1 bound to p65 only within the nucleus. By means of its SOCS box domain, SOCS1 operated as a ubiquitin ligase, leading to polyubiquitination and proteasomal degradation of nuclear p65. Thus, SOCS1 limited prolonged p65 signaling and terminated expression of NFκB inducible genes. Using mutants that lack either nuclear translocation or a functional SOCS box, this report identifies genes that are regulated in a manner dependent on the nuclear availability of SOCS1. Data show that beyond its receptor-proximal function in Jak/STAT signaling, SOCS1 also regulates the duration of NFκB signaling within the cell nucleus, thus exerting a heretofore unrecognized function.